색소찰옥수수 근동질 계통들에 대한 형태적 특성 연구 - 김해리(Hae Ri Kim), 사규진(Kyu Jin Sa), 박기진(Ki Jin Park), 남궁민(Min Nam-Gung), 모창연(Chang Yeun Mo), 이주경(Ju Kyong Lee) (Korean journal of breeding, 2020)
In this study, 14 agricultural and phenotypic traits were used to analyze morphological variations among 10 near-isogenic lines (NILs)of colored waxy maize and 2 parental lines (HW3 and HW9) of the hybrid cultivar “Mibaek 2.” The results of principal component analysisindicated that on the first principal component axis, seed coat color, R value, V value, days of tasseling, L* value, and days of silking greatlycontributed to the positive direction, whereas anthesis–silking interval and leaf width greatly contributed to the negative direction. On thesecond principal component axis, kernel row number and tassel color contributed to the positive direction, whereas setted ear length, ear length,and 100-kernel weight contributed to the negative direction. Thus, the morphological characteristics that greatly contributed to the first andsecond principal components might be useful for discrimination among the 10 NILs and 2 parental lines of “Mibaek 2.” Of the 10 NILsanalyzed, 16CLP26 and 16CLP16 were considered useful breeding material for the development of colored waxy maize varieties with relativelyhigh amounts of yield and anthocyanin. Collectively, these results are expected to provide useful information for the development and selectionof lines for breeding colored waxy corn varieties at the Maize Research Institute, Gangwon-do Agricultural Research and Extension Services. KCI Citation Count: 0